Incorporating Resource Constraints in Health Economic Evaluations: Overview and Methodological Considerations - Thokala, Praveen; Duarte, Henrique; Wright, Stuart; Husereau, Don; Durand-Zaleski, Isabelle; Lindgren, Peter; Postema, Roelien; Machnicki, Gerardo; Garrison, Louis (Université d'Ottawa | University of Ottawa, 2024)
Abstract It is well known that healthcare resource constraints influence the capacity to deliver care, affecting both the costs and outcomes of medical interventions. If these constraints are not adequately accounted for in economic evaluations, there may be a lack of understanding regarding the full impact of implementing health technologies, leading to decisions being made with suboptimal information. This paper offers an overview of the types of healthcare resource constraints and their potential effects, and introduces a framework grounded in operations research and health economics principles, outlining the methodological considerations for incorporating resource constraints into economic evaluations. Drawing from a literature review and advisory group feedback, three categories of resource constraints were identified: single-use resource constraints, reusable resource constraints and patient throughput constraints. The proposed framework outlines a comprehensive set of steps necessary for effectively incorporating constraints into health economic evaluations and details specific approaches and methodological considerations for each stage to ensure a more accurate and realistic assessment of health interventions. This paper also aims to raise awareness among payers and decision-makers with regards to the limitations of technology evaluations in a resource-constrained health system. Specifically, it suggests that health technology assessment agencies ought to offer guidance on incorporating constraints into the submissions they receive. Moreover, it advocates for a more comprehensive economic evaluation in economic assessments to fully capture an intervention’s value.